Research Misconduct: A Report from a Developing Country - Majid KHADEM-REZAIYAN; Maliheh DADGARMOGHADDAM (Tehran University of Medical Sciences, 2017)
Background: Cheating rate is rising and engages newer methods. This study performed to estimate the rate of research misconduct in the thesis of undergraduate and postgraduate medical students in 2015. Methods: In this cross sectional study, all undergraduate and postgraduate medical students graduated during the study period in 2015, from the School of Medicine, Mashhad University of Medical Sciences, Mashhad, Iran were asked to fill a small checklist anonymously. It consisted of two demographic questions and two other ones for estimation of research misconduct. All three major types of research misconduct were explained in the checklist. We used the Randomized Response Technique for sensitive question in this survey. We asked the respondent to choose one question randomly and answer to it. The probability of selection of each question was equal. Results: There were 149 filled questionnaires out of which 44 (31%) were graduated for General Practitioner, 63 (44%) for Residency, 31(21%) for Master Degree and 6 (4%) for Ph.D. Fifty-two percent (75) were male. More than half of participants were graduated between 2011 and 2012. The majority of participants were native (104, 81%). Undergraduate students had an estimation of 19% research misconduct in performing the thesis while this was 26% of postgraduate students. Males were nearly two times comparing to females in this issue (30% vs. 16%). Conclusion: This high estimation must be considered in future policy making about observing strictly on researches.